Problems of digital content definition - Stakhyra, Hanna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The theoretical approaches of scientists to the definition of the digital content concept are presented, the definitions of this concept, which are contained in the legislation of the European Union member countries of are analyzed. On the basis of generalization of existing approaches to the definition of this concept, the author’s definition of the concept of digital content is proposed